EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 1 BATUBULAN KANGIN: STUDI KASUS DAN ANALISIS SWOT - Gede Agung, Anak Agung; Chindytia; Jayanthi, Made Wahyu; Pita Yanti, Ni Putu Dian; Ginantri Setiari, Ni Kadek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of School-Based Management (SBM) implementation at SD Negeri 1 Batubulan Kangin, Gianyar Bali, to identify the roles of stakeholders involved, and to examine supporting and inhibiting factors through SWOT analysis. This study applies a qualitative approach with a case study design. Data were obtained through in-depth interview with Gede Tunas (Grade 4 homeroom teacher) conducted on April 21, 2026, and analyzed using thematic analysis and SWOT matrix to map internal and external factors affecting SBM effectiveness. SD Negeri 1 Batubulan Kangin has effectively implemented SBM as evidenced by structured RKAS document management, democratic decision-making through musyawarah mufakat, and structured thematic daily programs (Monday–Saturday). The principal's leadership combining instructive and participative approaches, along with a strong family-oriented school culture, constitutes the primary internal strength. Key challenges include synchronizing stakeholder visions and dependency on internal teaching staff for olympiad coaching. This study contributes a contextualized SWOT-based SBM effectiveness analysis integrated with multi-stakeholder role mapping at the elementary school level in Bali, offering a localized model of SBM implementation applicable to culturally distinctive educational settings.